DEVELOPING VOCABULARY BOOK BASED ON CROSSWORD PUZZLE FOR VOCABULARY MASTERY AS MEDIA OF VOCABULARY INSTRUCTION FOR JUNIOR HIGH SCHOOL - Sari, Agatha Tantri windu; Qomar, Aulia Hanifa (Jurnal Pedagogy, 2017)
The main objective of the research is to develop picture media for vocabulary mastery based on crossword puzzle as a media of vocabulary instruction. The research was a research and development (R&D) study. This research is formative research. The steps in this research were conducting self-evaluation, getting expert review and one-to-one, small group, and filed test. The research object of this study is students of eight grade in SMP Muhammadiyah 3 Metro and SMP Negeri 10 Metro. Based on explanation above, it is conclude that by using vocabulary book based on crossword puzzle is very good and can help students in learning vocabulary and the students got a new knowledge.